PELABELAN ODD-GRACEFUL PADA GRAF PRODUK SISIR - Daniel, Juan; Barack, Zeveliano Zidane; Ilham, Pandu Setya; Sugeng, Kiki Ariyanti (Jurusan Matematika FMIPA Universitas Jember, 2022)
Gnanajothi defined a graph with edges to be odd-graceful if there is an injective function such that if every edge is labelled with the resulting edge labels are . She proved that the graph obtained by joining one pendant to every vertex in is odd-graceful if and only if is even. In this paper, we extend her results by proving that is odd-graceful if and only if is even.Keywords: Vertex-labelling, odd-graceful, cycleMSC 2020: 05C78